Character and Learning Outcomes of Civics in VCT Learning Assisted by Audio Visual Media - Ardika, Ngurah Putu; Agustiana, I Gusti Ayu Tri; Dibia, I Ketut (Universitas Pendidikan Ganesha, 2022)
This research was conducted because of Civics' low character and student learning outcomes due to ineffective use of learning models and media. This study aims to analyze whether there is an effect of the VCT learning model assisted by audio-visual media on the character and learning outcomes of fifth-grade Civics students. This research is a quasi-experimental study with a post-test-only control group design. The research population was 170 students, with a sample of 74 students determined by group (intact group) with the Gugus random sampling technique. Student character data was collected by questionnaire, and an objective test collected student learning outcomes of Civics. The analysis technique uses descriptive analysis and manova. The calculation results of the average character score of 85.10 are in the very good category. Civics learning outcomes of 81.90 are in the very good category, while the score obtained in the control class is the character score of 80.29, including the very good category. The Civics learning outcome score of 68.14 is in a good category. Based on these results, it can be concluded that the VCT learning model assisted by audio-visual media positively affects fifth-grade Civics' character and learning outcomes. Therefore, the problem of the gap between the expectations of the 2013 curriculum and the facts in the field regarding the character and learning outcomes of Civics for fifth graders has been resolved by the VCT learning model assisted by audio-visual application media.